2020
DOI: 10.3390/ijerph17020501
|View full text |Cite
|
Sign up to set email alerts
|

Factors Shaping the Lived Experience of Resettlement for Former Refugees in Regional Australia

Abstract: Refugees experience traumatic life events with impacts amplified in regional and rural areas due to barriers accessing services. This study examined the factors influencing the lived experience of resettlement for former refugees in regional Launceston, Australia, including environmental, social, and health-related factors. Qualitative interviews and focus groups were conducted with adult and youth community members from Burma, Bhutan, Sierra Leone, Afghanistan, Iran, and Sudan, and essential service providers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 39 publications
4
41
0
Order By: Relevance
“…Racism impacted on people's lives, particularly those from Africa, undermining a sense of belonging, safety, and in turn effective integration [76,77]. There is a substantial literature highlighting the detrimental impact of racism on health in general [78][79][80][81][82] as well as for refugees specifically [57,[83][84][85][86], including in rural resettlement [41,76,77,87]. Community development initiatives such as community arts projects and anti-racism curriculum in schools are important in these contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Racism impacted on people's lives, particularly those from Africa, undermining a sense of belonging, safety, and in turn effective integration [76,77]. There is a substantial literature highlighting the detrimental impact of racism on health in general [78][79][80][81][82] as well as for refugees specifically [57,[83][84][85][86], including in rural resettlement [41,76,77,87]. Community development initiatives such as community arts projects and anti-racism curriculum in schools are important in these contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Unemployment and underemployment are key issues more broadly in rural towns in Australia and internationally and have also been identified as particular issues for regional refugee resettlement nationally [9,41,58,[87][88][89][90] and internationally [11]. Difficulties in accessing secure long-term employment affected resettlement and integration experiences of the participants in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It was also identified that WoRB have additional barriers to overcome in an attempt to develop their English proficiency skills, including being at a disadvantage within a learning context. The need for language programs for refugee populations in regional areas to be flexible has been highlighted by Smith, Hoang, Reynish, McLeod, Hannah, Auckland, Slewa-Younan and Mond [ 3 ], with the current study further emphasising that flexibility, in regard to the how the language program is delivered and the amount of hours available, is paramount when supporting WoRB in an educational context. Building on the need identified by Smith, Hoang, Reynish, McLeod, Hannah, Auckland, Slewa-Younan and Mond [ 3 ], the current study emphasised the particular vulnerability of WoRB in the educational context, and that the current English program in regional areas is insufficient.…”
Section: Discussionmentioning
confidence: 93%
“…In 2019, the United Nations estimated that 79.5 million individuals had been forcibly displaced globally, with approximately 1.4 million individuals of refugee background in urgent need of resettlement [ 1 , 2 ]. Resettlement is the process whereby individuals of refugee background move from the country where they have sought protection to a different country where they have been granted long-term or permanent residence status [ 2 , 3 ]. Although resettlement holds the potential for safety, researchers have demonstrated that the process of resettlement also comes with a multitude of challenges, as individuals of refugee background are exposed to cultural contexts and social and economic environments vastly different to their country of origin [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation